Differential expression and bioinformatics analysis of circRNA in osteosarcoma. Issue 5 (17th May 2019) - Xi, Yizhe; Fowdur, Mitra; Liu, Yun; Wu, Hao; He, Maolin; Zhao, Jinmin
Abstract : Aim: This research aims to investigate the expression profile of circRNA in osteosarcoma and to identify the underlying pathogenesis core genes of osteosarcoma. Methods: Illumina HiSeq was used to screen differentially expressed circRNAs between the tumour tissues and paracancerous tissues of three osteosarcoma patients. Bioinformatics analysis was used to analyse their potential functions. Five differentially expressed circRNAs were selected to detect the relative expression level in tumour and paracancerous tissues of ten osteosarcoma patients by real-time PCR. The databases such as DisGeNET and miRWalk were used to collect related genes or miRNAs. Results: A total of 259 differentially expressed circRNAs were evaluated in patients with osteosarcoma, of which 132 were up-regulated and 127 were down-regulated. Compared with that in paracancerous tissues, circ_32279 and circ_24831 were significantly down-regulated while circ_2137 and circ_20403 were significantly up-regulated in osteosarcoma tissues. The differential expression of circRNA is closely linked to biological processes and molecular functions. The difference in circRNA was mainly linked to the 'phosphatidylinositol signalling system' signal pathway and the 'inositol phosphate metabolism' signal pathway. Conclusion: The present study identified a profile of abnormal regulation of circRNA in osteosarcoma. Bioinformatics analysis indicates that the deregulated circRNAs may be related to the occurrence and development of osteosarcoma.